Building independent character throught project-based learning (PJBL) in grade VIII junior high school students - Wahyuni, Anik; Restian, Arina; Agus Tinus (CV. FOUNDAE, 2025)
Background: Student independence has increasingly become a core objective in contemporary education, yet its development is strongly shaped by the instructional strategies employed by teachers. Although innovative learning models such as Project-Based Learning (PJBL) offer strong potential to empower learners, their success largely depends on the extent to which teachers prepare, facilitate, and sustain the learning process. Without systematic planning and thoughtful implementation, even the most promising learning model may fall short of producing meaningful character development. Aim: This study seeks to describe the implementation process of PJBL and analyze how the model contributes to fostering independent character among Grade VIII junior high school students. Method: A descriptive qualitative research design was applied. Data were obtained through classroom observations, semi-structured interviews with teachers and students, and documentation of project activities, including learning artifacts, student reflections, and project outputs. All data were analyzed using an inductive approach to identify patterns related to student independence. Results: The findings indicate that continuous engagement in PJBL activities strengthens several aspects of student independence. Students demonstrate increased initiative in planning tasks, greater responsibility in meeting project deadlines, improved capacity to make decisions, and stronger problem-solving abilities. They also exhibit enhanced time-management skills and active participation during group presentations and collaborative work sessions. Conclusion: Overall, the study confirms that PJBL is not only beneficial for achieving cognitive learning outcomes but also serves as an effective approach for cultivating deeper independence among junior high school students. The model is therefore relevant and highly recommended for instructional practices that aim to promote autonomy and self-regulated learning.